Multi-Antigen Viral-Vectored Vaccine Protects Against SARS-CoV-2 and Variants in a Lethal hACE2 Transgenic Mouse Model - Stone, Shannon; Elsharkawy, Amany; Burleson, J. D.; Hauser, Mary; Domi, Arban; Kumari, Pratima; Nabi, Zainab; Natekar, Janhavi P.; Porto, Maciel; Backstedt, Brian; Newman, Mark; Oruganti, Sreenivasa Rao; et al. (Vaccines (Basel), 2025)
Widespread and rapidly evolving SARS-CoV-2 posed an unprecedented challenge to vaccine developers. GeoVax has designed a multiantigen SARS-CoV-2 vaccine, designated GEO-CM02 based on a Modified Vaccinia Virus (MVA) vector that expresses spike (S), membrane (M), and envelope (E) antigens. This experimental vaccine was tested in the hACE2 transgenic mouse model to assess immunogenicity and efficacy. Administration of the vaccine in a two-dose regimen elicited high levels of neutralizing antibodies and provided complete protection, effectively reducing lung, olfactory bulb, and brain viral load and reducing lung inflammation following infection with original B.1 virus and the B.1.1.529 variant. In addition, GEO-CM02 conferred 80% protection against a lethal infection with the B.1.351 variant. GEO-CM02 vaccine efficacy studies also demonstrated a complete level of vaccine-induced protection with a single dose against the original B.1 virus and B.1.1.529 variant. GEO-CM02 effectively elicited functional T-cell responses in both prime and prime–boost groups. These data indicate that vaccination with the GEO-CM02 vaccine can induce immune responses that protect against severe disease induced by SARS-CoV-2 and its variants in a highly relevant pre-clinical model.